The determinants of profit management practices in Algerian companies ‏ ‏Listed on the Stock Exchange (2007-2009)‎ - Chawchi, Kahina (Dirassat Journal Economic Issue, 2020)
management in Algerian listed companies during the period 2007-2009. Using multiple linear regressions to test the effect of the independent variables on the dependent variable. The results suggested a significant positive relationship between debt and discretionary accruals; Also there is a significant negative relationship relation between the liquidity of the company and discretionary accruals, the company profitability have no effect on earnings management.